Art in Britain 1660-1815 - Solkin, David H. (New Haven : Yale University Press, 2015)
"Art in Britain 1660-1815 presents the first social history of British art from the period known as the long 18th century, and offers a fresh and challenging look at the major developments in painting, drawing, and printmaking that took place during this period. It describes how an embryonic London art world metamorphosed into a flourishing community of native and immigrant practitioners, whose efforts ultimately led to the rise of a British School deemed worthy of comparison with its European counterparts. Within this larger narrative are authoritative accounts of the achievements of celebrated artists such as Peter Lely, William Hogarth, Thomas Gainsborough, and J.M.W. Turner. David H. Solkin has interwoven their stories and many others into a critical analysis of how visual culture reinforced, and on occasion challenged, established social hierarchies and prevailing notions of gender, class, and race as Britain entered the modern age. More than 300 artworks, accompanied by detailed analysis, beautifully illustrate how Britain's transformation into the world's foremost commercial and imperial power found expression in the visual arts, and how the arts shaped the nation in return"--Provided by publisher
boek